Goods trade liberalization under the ASEAN Economic Community effects on the Philippine economy. - Clarete, Ramon L.
The authors discusses the economy-wide effects of the Asean Free Trade Area (AFTA) on the Philippine economy. Notwithstanding the contraction of production in the majority of industries, the country comes out a net gainer in aggregate output. This implies that, overall, the Philippines is slightly better off with the preferential trade liberalization. Therefore, policies related to providing information and new market opportunities, organizing value chains, facilitating coordinated investments along the chain, clustering of related small and medium enterprises to boost external economies, and providing information to employers and workers of job opportunities, including training, are important. The empirical literature in developing countries shows that the employment response of trade reforms is dependent on infrastructure, trade facilitation measures, and other policies.